The Experimental Analysis for Different Rod Configurations of Grounding System. - Noordin, Muhammad Izzat Imran; Othman, Nordiana Azlin (Evolution in Electrical and Electronic Engineering, 2023)
Generally, grounding systems secure electrical equipment and people by channeling fault currents to the ground. The location of the electrode is crucial for a small grounding resistance value. Measurements are required to determine the resistance value. Earthing resistance value is affected by planting depth and electrode location. This paper investigates the relationship between electrode arrangement and electrode depth for a low-resistance earthing system. Also conducted in this paper is the determination of soil types found in Universiti Tun Hussein Onn Malaysia (UTHM) based on the measurement of resistivity values. The installation of this grounding system was conducted in Tun Fatimah’s residential college at UTHM with different methods which are a single grounding rod, two parallel grounding rods and three parallel grounding rods. Each of these methods is planted at a different depth particularly 1.5, 3.0 and 4.5 meters. The performance of an earthing system is determined by factors such as electrode depth, soil conditions, soil types and installation types. It is found that the resistance value for the depth of 3 rods planted with the single grounding rod method (4.5 meters) is 0.612 ohms while the resistance value for the depth of 1.5 meters with the three parallel grounding rod method is 1.8 ohms. Thus, it can be concluded that the deeper the electrode, the lower the ground resistance. Deeper electrode implantation significantly reduces the resistance value compared to parallel implantation.